Analisis Reduksi Suara dan Kuat Tarik Komposit Beton Serat Gedebok Pisang Hasil Delignifikasi Dengan Pelarut Natrium Hidroksida (Naoh) - Muhammad Rouf Suprayogi; Annisa Mufida; Edwin Azwar (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
In composite science, desirable materials that are lighter but have the power and quality that can match or even exceed the material that has been there before. The purpose of this study was to investigate the effect of cellulose fiber addition from banana gedebok to tensile strength, compressive strength and damping of concrete composite sound. To achieve this objective, mixing of cellulose fibers with K-275 quality concrete mix with variation of 0% and 5% substitution in which the cellulose is varied in powder and wicker form. Delignification of lignin content from banana gedebok was done by soaking and drying method without any variation and yielding powder having cellulose content of 13,0388%, hemicellulose 18,2796% and lignin 0,6684%. This study produces concrete composites that have a tensile strength and a compressive strength lower than that of normal concrete. Normally reinforced concrete tensile strength value 94.5 kg / cm2, 71.4 kg / cm2 cellulose powder concrete and 90.3 kg / cm2 cellulose woven concrete. Normal concrete compressive strength value 334,22 kg / cm2, cellulose powder concrete 215,7 kg / cm2, and cellulose webbing concrete 157,98 kg / cm2. As for the power damping sound of cellulose webbing concrete has the highest damping power compared to other concrete with the absorbed sound intensity that is 52-68 dB